Large-scale serological survey on Mycobacterium avium subsp. paratuberculosis infection in sheep and goat herds in Sicily, Southern Italy - Di Marco Lo Presti, Vincenzo; Ippolito, Dorotea; Migliore, Sergio; Tolone, Marco; Mignacca, Sebastian Alessandro; Marino, Anna Maria Fausta; Amato, Benedetta; Calogero, Rosita; Vitale, Maria; Vicari, Domenico; Ciarello, Flavia Pruiti; Fiasconaro, Michele (Frontiers in Veterinary Science, 2024)
Paratuberculosis (PTB) is a worldwide chronic, contagious enteric disease caused by Mycobacterium avium subsp. paratuberculosis (MAP) mainly affecting ruminant species. PTB is a WOAH-listed disease with direct and indirect economic losses in the livestock sector, negative impact on animal welfare and significant public health concerns. In spite of this, MAP prevalence in small ruminants is still unknown and the prevalence appears to be underestimated in many countries. The aim of this study is providing a first large-scale serological survey on MAP infection in small ruminants in Sicily, a region of southern Italy with the 11.3 and 8.9% Italian national heritage of sheep and goats respectively. For this purpose, we analyzed a total of 48,643 animals reared in 439 flocks throughout Sicily. MAP seroprevalence was estimated both at herd-level and animal-level within breeds reared in all the nine sampled provinces. Our results revealed a high overall apparent prevalence at herd-level of 71.8% in sheep and 60.8% in goat farmms with an animal-level prevalence of 4.5 and 5.1% in sheep and goats respectively. Significant statistical differences were found between the provinces and within the breeds both in sheep and goats. Our study provides the first large-scale serological survey on PTB infection in small ruminants in Sicily and showed a high prevalence of disease depending to the species, breed and province. This study represents the first step to better understand the MAP epidemiology in a typical Mediterranean breeding contextSicily, suggesting the need of in-depth study on the herds risk factors, including the eventual presence of candidate genes for resistance/susceptibility to PTB in native breeds.